PENGARUH PROFESIONALISME DAN LOCUS OF CONTROL TERHADAP KINERJA AUDITOR DI KANTOR AKUNTAN PUBLIK PROVINSI BALI - Kusnadi, I Made Gheby; Suputra, Dewa Dharma (E-Jurnal Akuntansi; Vol 13 No 1 (2015), 2015)
Widespread public accounting firm needs an independent party, demanding a public accounting profession to increase the performance, so that the resulting output can be relied upon for those in need. Performance Public Accounting Firm (KAP) quality is largely determined by the performance of the auditor. Auditor performance is a form of work carried out to achieve a better work or toward the achievement of organizational goals. This research was conducted at 8 KAP with a total sample of 40 auditors. This study uses nonprobability sampling technique saturated sample or census. Methods of data collection in the form of a survey method with data collection using kwisioner. Obtain partial test (1) professionalism positive effect on the performance of the auditor, (2) internal locus of control have positive influence on the performance of auditors, (3) external locus of control negative effect on the performance of auditors.
Keywords: Professionalism, Locus of Control Internal, External Locus of Control, Performance Auditor